A BIFURCATION APPROACH FOR ATTRITIONAL AND LARGE LOSSES IN CHAIN LADDER CALCULATIONS. Issue 1 (13th November 2013) - Riegel, Ulrich
Abstract We introduce a stochastic model for the development of attritional and large claims in long-tail lines of business and present a corresponding "chain ladder-like" IBNR method which allows the use of claims payment data for attritional and claims incurred data for large losses. We derive formulas for the mean squared error of prediction and apply the method to a German motor third party liability portfolio.